Review of the genus Tetralicia (Hemiptera: Aleyrodidae) and description of two new species of whiteflies found on avocado trees in Peru - V., Luis Valencia; Evans, Gregory A. (Zootaxa, 2024)
Two new species, Tetralicia sawyeri n. sp. and Aleuroplatus martini n. sp. found on avocado (Persea americana) trees in Peru are described and illustrated. The synonymy of Aleuropleurocelus Drews & Sampson, 1956 n. syn. with Tetralicia Harrison, 1917 is proposed and a review and an illustrated key to the 39 species of Tetralicia of the world based on characteristics of the puparia is provided. Thirty-three species are transferred from Aleuropleurocelus to Tetralicia. A lectotype is designated for Aleurodes abnormis Quaintance, 1900. Aleurotrachelus gratiosus Bondar, 1923 is transferred to the genus Aleuroplatus. Paracarniella mexicana (Distant) and Adparaproba cf. yungensis Carvalho (Hemiptera: Miridae) are recorded for the first time in Peru and are important predators of both new whitefly species. Other natural enemies of these whiteflies found in the study include predatory species: Nephaspis isabelae González (Coccinellidae), Chrysoperla sp., Ceraeochrysa sp. (Chrysopidae) and Gasteracantha cancriformis L. (Araneidae) as well as Encarsia brasiliensis Hempel, a common whitefly parasitoid in the Neotropics. A key to the New World genera of whiteflies similar to Aleuroplatus and Tetralicia is provided.